Langmuir Monolayers of Polyphenyl Carboxylic Acids - Dynarowicz-Ła̧tka, Patrycja; Dhanabalan, Anantharaman; Cavalli, Ailton; Oliveira Jr., Osvaldo N. (American Chemical Society (ACS), 2000)
A series of 4′-substituted (methyl, phenyl, biphenyl, toluilyl, nitro, cyano, and p-nitrophenyl) 5′-phenyl-m-terphenyl-4-carboxylic acids (PTCAs) have been synthesized, and their Langmuir monolayers were characterized using surface pressure and surface potential isotherms under a variety of experimental conditions. A long plateau appears at the pressure-area isotherms for most compounds, which is attributed to the tilting of molecules upon compression. A model is presented for the molecular arrangements which explains the decrease in dipole moment in the plateau region. As expected, the monolayer stability was higher for derivatives with more hydrophobic substituents, whereas the introduction of an additional hydrophilic group, viz. -CN or - NO2, in the parent PTCA molecule yielded negative surface potentials since the latter groups contributed negatively, in opposition to the positive contribution from the COOH group.